The influence of price product quality and brand image on purchase decisions bear brand milk - Nurfahrisya Adisti Anggraeni; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
The aim of this study was to analyze the partial influence between Price, Product Quality, and Brand Image on Purchasing Decisions on Bear Brand Milk products at Pelita Bangsa University. The sampling method used by researchers is nonprobability sampling with an accidental sample method with a sample size of 100 respondents who are consumers who have purchased Bear Brand Milk at Pelita Bangsa University. The research was conducted using SPSS version 25. To collect data, researchers conducted a questionnaire distribution survey and literature study. The type of research used is quantitative. The analysis methods used are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing. the results of this study are three independent variables, namely price, product quality and brand image partially have a positive and significant effect on purchasing decisions